Prolonged Toxic Encephalopathy following Accidental 4-Aminopyridine Overdose - Maria Ballesta Méndez; Vincent van Pesch; Arnaud Capron; Philippe Hantson (Case Reports in Neurological Medicine)
Background. 4-Aminopyridine (4-AP) is a drug that is used to improve motor fatigue in patients suffering from multiple sclerosis (MS). Medication error can occur, as commercial preparation may not be available in some countries. Case Presentation. A 58-year-old woman with progressive MS presented with status epilepticus. She was receiving 4-AP for more than 3 years. The symptoms started soon after the ingestion of a single pill that was supposed to contain 10 mg 4-AP, but further investigations revealed that each pill had been inadvertently prepared with an 100 mg 4-AP concentration. The patient was admitted to the intensive care unit (ICU) for appropriate management (orotracheal intubation, sedation, and antiepileptic drugs). The first electroencephalogram (EEG) showed abundant irregular spike-waves on the left central regions. Neurological condition gradually improved from day 7, while the EEG did not reveal any more electrical seizures but was still consistent with toxic encephalopathy. The patient stayed in the ICU until day 13. At discharge from the rehabilitation ward (2.5 months later), the patient had not yet recovered her previous cognitive and functional condition. Conclusion. A single 100 mg 4-AP accidental overdose may cause serious immediate complications, with a slow and incomplete neurological recovery.